6-Benzylaminopurine (BAP) and Methyl Jasmonate (MeJa) Affect Sex Expression, Flowering Time and Flowering Intensity in Cultivated Yam Dioscorea rotundata (Poir.) - Narcisse Denadi; Aline Vanhove; Jeanne Zoundjihékpon; Christophe Gandonou; Muriel Quinet (Applied Biosciences)
Cultivated yam (Dioscorea rotundata) is a staple tuber crop in West Africa which is mainly vegetatively propagated. Although the majority of yam cultivars flower, the control of their sexual reproduction remains largely unknown despite its importance for plant-breeding programs. While described as a dioecious species, yam has several monoecious (mix) cultivars that are often subject to spontaneous sex changes. This study aims to evaluate the impact of phytohormones on sex expression and flower development in cultivated yams D. rotundata. Exogenous applications of 1 mM 6-benzylaminopurine (BAP) and 1 mM methyl jasmonate (MeJa) were performed on seedlings of female (Gnidou, Anago), male (Flou) and mix (Katala and Laboko) cultivars. The mix cultivars produced monoecious, male and female plants while the female and male cultivars had rather stable sex. Our results showed that MeJa exhibited a significant masculinising effect in mix cultivars and induced inflorescence and flower malformations in female cultivars (56% in Gnidou and 37% in Anago). Most malformations were inflorescence branching and sterile flowers (non-differentiated ovary) with extra cycles of sepals. Moreover, MeJa reduced flowering time in the cultivars of all sexes and increased the number of inflorescences per plant as well as the number of flowers per plant. Our results showed that BAP reduced the flowering time, synchronized flowering in female plants and increased the number of inflorescences per plant in monoecious plants. However, our results did not allow for strong conclusions regarding the effect of BAP on sex expression due to the high proportion of female flowering in both the control and BAP-sprayed plants. Nevertheless, we did not observe any masculinising effect for BAP. Further research that would highlight hormone and homeotic gene interactions in flowering could be of key interest in understanding the hormonal control of sex in cultivated yams D. rotundata.